Self-reported mental health in children ages six to 12 across eight European countries - Gölitz, Dietmar; et al. (European Child & Adolescent Psychiatry, 2018)
Background Worldwide, approximately one in eight children or adolescents suffer from a mental disorder. The present study was designed to determine the self-reported prevalence of mental health problems in children aged 6 to 11 years across eight European countries including Italy, France, Germany, the Netherlands, Lithuania, Bulgaria, Romania, and Turkey. Methods Data were drawn from 6340 children participating in the School Children Mental Health in Europe (SCHME) study and a large cross-sectional survey in France. Self-reported child mental health was assessed using the Dominique Interactive (DI). Results Overall, 22.6% of children were identified per their own evaluation as having at least one mental disorder, ranging from 16.4% in the Netherlands to 27.9% in Bulgaria. The prevalence of internalizing disorders was 18.0% across countries and ranged from 11.8% in the Netherlands to 24.3% in Turkey. The prevalence of externalizing disorders was lower with an average of 8.5%, ranging from 3.5% in Turkey to 14.9% in France. Important between-country differences were revealed after controlling for a number of sociodemographic and parental variables Conclusions Across Europe, close to one in five children reports internalizing problems and one in twelve children externalizing problems. The stark differences between countries suggest varying degrees of emotional distress.
Keywords: SCMHE; 1 Grundschulentwicklung